2019
DOI: 10.1111/ecc.13150
|View full text |Cite
|
Sign up to set email alerts
|

Lay people's psychological reactions and helping intention after friends’ cancer disclosure: An exploratory analysis using vignettes

Abstract: Objectives Stigma, anticipated responses from others, and their relationships may affect patients’ decision‐making of cancer disclosure. However, little research has explored responses to cancer disclosure and the outcome from receivers’ perspectives who had stereotypic views of cancer. This vignette study aimed to explore how lay people with negative attitude to cancer would react to the friend's cancer disclosure. Methods A cross‐sectional survey study was conducted in community organisations. Of 161 recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Research investigating stigma-related experiences of patients with cancer with their friends is limited. However, negatively affected friendships were detected in other populations 38 , and one study suggested that the hardship in accepting a friend's cancer diagnosis could be a factor in this 39 . Further studies examining this in the NL population can help us identify the root cause and thus enable formulation of effective ways of minimizing friendship loss and its negative consequence on individuals diagnosed with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating stigma-related experiences of patients with cancer with their friends is limited. However, negatively affected friendships were detected in other populations 38 , and one study suggested that the hardship in accepting a friend's cancer diagnosis could be a factor in this 39 . Further studies examining this in the NL population can help us identify the root cause and thus enable formulation of effective ways of minimizing friendship loss and its negative consequence on individuals diagnosed with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The same study also reported that support from friends helped to decrease depressive symptoms among young adults (Fukuoka & Hashimoto, 1997). Research about illness‐disclosure behaviour among informal caregivers, however, has almost exclusively investigated patient–partner relationships, with little attention paid to patient–friend relationships (Tsuchiya, 2019).…”
Section: Introductionmentioning
confidence: 99%